PENGARUH PEMBERIAN ABU SEKAM PADI DAN KOMPOS JERAMI PADI TERHADAP SIFAT KIMIA TANAH ULTISOL PADA TANAMAN JAGUNG MANIS - Fitra Syawal Harahap; Hilwa Walida; Roswita Oesman; R Rahmaniah; Iman Arman; Makruf Wicaksono; Dahrul Aman Harahap; Rosmidah Hasibuan (Jurnal Tanah dan Sumberdaya Lahan, 2020)
This study aimed to determine the effect of rice straw compost and rice husk ash on some chemical properties of an Ultisol soil under sweet corn plant. This study was conducted at the Labuhan Batu Rantau Prapat University Campus Land and the PT. Socfindo Laboratory. The design used in this study was a randomized factorial design consisting of two factors with two replications. The first factor was the application of rice husk ash with four dose levels (g 5 kg-1 of soil), i.e. P0 (0), P1 (10), P2 (20), and P3 (30). The second factor was the application of rice straw compost with four dose levels (g 5 kg-1 of soil), i.e. J0 (0), J1 (25), and J2 (50), J3 (75). Results of this study indicated that the application of rice straw compost significantly increased soil organic-C and available P contents, as well as plant height, plant dry weight, N and P uptake by the plant. The treatments, however, did not significantly increase soil pH and total-N content. The application of rice husk ash significantly increased soil organic-C content and N uptake by the plant, but it did not significantly increase pH, available P content, and total N content of the soil.